THE DEVELOPMENT OF A LEARNING MANAGEMENT MODEL BASED ON COMMUNICATIVE LANGUAGE TEACHING AND TASK BASED LEARNING TO ENHANCE COMMUNICATIVE COMPETENCE FOR GRADE VI STUDENTS - Cacic, Sukumapon; Kaewurai, Wareerat (Journal of Education and Innovation, 2020)
The research was 1) to study learning management to enhance grade VI students’ communicative competence, 2) to construct a learning management model based on Communicative Language Teaching and Task Based Learning and study its qualities, 3) to implement the learning management model and study its results on (1) students’ communicative competence after using the learning management model, (2) students’ communicative competence by comparing pretest and posttest scores, and (3) students’ satisfaction toward the learning management model. The research consisted of 3 steps of research and development processes: 1) studying teachers’ learning management and the way to enhance students’ communicative competence by conducting an interview with 5 English teaching experts, 2) constructing a learning management model which was evaluated by 5 experts and studying its quality by implementing it to a pilot group of 30 grade VI students to study an effective index, and 3) implementing the learning management model. Specific sample used for the experiment were 32 students of Banbung School. The research results were as follows: 1. The learning management as a way to enhance student’s communicative competence should provide language learning opportunities as well as include various communicative activities. The tasks should be attractive, enjoyable and suitable to learners’ age. Moreover, the assessment and evaluation of learning management should follow the Common European Framework of Reference for Languages (CEFR) and incorporate with school curriculum and context. 2. The learning management model consisted of principles, goals, contents, instructional processes, and measurements and evaluations. The learning management model consisted of 3 components; 1) presentation (lead in, elicitation and explanation), 2) practice, and 3) production (pre-task, during-task and post-task). The experts agreed to the quality of the learning management model at the high level (4.33 of 5-level scales). The effective index of the learning management model was .5327. 3. When the learning management model was implemented, it was found that: 3.1 The students’ listening competence was at fairly good level, speaking competence was at satisfactory level, reading competence was at sufficient level and writing competence was at marginal pass level. The overall competence was at satisfactory level. 3.2 The students’ communicative competence after learning through the learning management model was higher than before learning at the 0.05 level of statistical significance. 3.3 The students’ satisfaction toward the learning management model was at a high level (4.21 of 5-level scales).